SPATIAL SELECTIVITY OF EARTHQUAKE'S PRECURSORS - Rokityansky I.I. (My University, 2006)
Multiparameter monitoring of earthquake's (EQ) precursors reveals their selective localization (selectivity), i.e. a precursor can be observable in relatively small selected sensitive area(s) and not observable over remaining vast region. Selectivity and long distance appearance of precursors are rather strange and difficult for explanation, if the Earth is considered as uniform or horizontally layered, but quite natural for the real Earth, which is saturated by inhomogeneities and channels of different scale and nature. Three kinds of channels are proposed for explanation of selectivity: electrically conductive path (for electrical precursors), hydraulic channel and magma intrusion in the stage of emplacement. © 2006 Elsevier Ltd. All rights reserved.
Keywords: CHANNELING; CONDUCTIVITY STRUCTURE; EARTHQUAKE'S PRECURSOR; MAGMA EMPLACEMENT; SPATIAL SELECTIVITY